2009
DOI: 10.1073/pnas.0900180106
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant N-terminal domain fully restores deactivation gating in N-truncated and long QT syndrome mutant hERG potassium channels

Abstract: Human ether á go-go related gene (hERG) potassium channels play a central role in cardiac repolarization where channel closing (deactivation) regulates current density during action potentials. Consequently, mutations in hERG that perturb deactivation are linked to long QT syndrome (LQTS), a catastrophic cardiac arrhythmia. Interactions between an N-terminal domain and the pore-forming ''core'' of the channel were proposed to regulate deactivation, however, despite its central importance the mechanistic basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
164
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(177 citation statements)
references
References 41 publications
12
164
1
Order By: Relevance
“…Therefore, it sheds significant new insight into the molecular basis of the protein-protein interactions between the N-terminal distal regions and the S4-S5 linker involved in the control of gating properties and hormonal modulation of hERG (1,2,24,(27)(28)(29)(30)(31)(32)(33)36).…”
Section: Herg N-terminal Interactions With the S4-s5 Linkermentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it sheds significant new insight into the molecular basis of the protein-protein interactions between the N-terminal distal regions and the S4-S5 linker involved in the control of gating properties and hormonal modulation of hERG (1,2,24,(27)(28)(29)(30)(31)(32)(33)36).…”
Section: Herg N-terminal Interactions With the S4-s5 Linkermentioning
confidence: 99%
“…It has been repeatedly proposed that an interaction between N-terminal domains and the S4-S5 linker is the cause of the strong influence exerted by the N terminus in the gating properties (1, 16, 23-25, 27-33, 37-39). Nevertheless, evidence for this interpretation is mostly indirect, including (i) the essential role of the S4-S5 linker coupling voltage sensor activation to the activation gate (38,40), (ii) the strong parallelism between the alterations in gating caused by mutations in the N terminus and those in the S4-S5 linker (1, 16, 24, 27-33, 37, 41), (iii) the prevention of deactivation slowing by the N terminus after mutation of Gly-546 in the S4-S5 linker to cysteine and its subsequent modification by the addition of the sulfhydryl reagent N-ethylmaleimide (29), (iv) the impairment of the cytoplasmic domain-dependent modulation of gating in response to hormonal treatments by single-point mutations in the initial portion of the S4-S5 linker (2), (v) the restoration of slow deactivation gating by the addition of synthetic or recombinant N-terminal domains to channels lacking the N terminus (28,31,32), and (vi) the closer positioning of the N-terminal-most segments of the hERG N terminus toward the transmembrane channel core structures compared with other cytoplasmic regions of the channel (3). Note, however, that despite these findings, a direct demonstration of a physical interaction between the distal portion of the N terminus and the S4-S5 linker in the entire channel protein is lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that slow deactivation could be restored in LQT2 mutant hERG R56Q channels by application of a genetically encoded PAS domain (NPAS) in Xenopus oocytes (15). Here, we sought to determine whether NPAS was a general mechanism for rescue of LQT2 mutant channels.…”
mentioning
confidence: 99%
“…hERG channels containing LQT2 mutations in the PAS domain (hERG PAS-LQT2) exhibit robust currents when studied in Xenopus oocytes (6,(13)(14)(15); however, most channels with LQT2 mutations located outside the PAS domain do not have measurable currents and show defects in maturation and trafficking when studied in mammalian cells (12, 16 -21). As only 5 hERG PAS-LQT2 channels have been functionally characterized in mammalian cells (20 -24), the mechanism for how PAS domain mutations disrupt hERG function when expressed in more physiological conditions remains unclear.…”
mentioning
confidence: 99%